Family Resilience and Psychological Responses to COVID-19: A Study of Concordance and Dyadic Effects in Singapore Households - Ho, Yi-Ching Lynn; Chew, Mary Su-Lynn; Mahirah, Dhiya; Thumboo, Julian (Frontiers in Psychology, 2022)
The impacts of COVID-19 may be magnified in a shared environment like the household, especially with people spending extended time at home during the pandemic. Family resilience is the ability of a family to adapt to crisis and can be a protective factor against stress and negative affect. While there have been calls to address family resilience during the pandemic, there is a lack of empirical study on its benefit. In this dyadic observational study, we sought to investigate the concordance of family members’ psychological responses to COVID-19, whether dyad members’ risk factors (COVID-19 exposure and financial impact) mutually affected each other’s psychological responses, and importantly whether family resilience was a significant factor in these responses. 200 family dyads from the same household completed the Family Resilience Assessment Scale and questionnaires on COVID-19 threat perception, impacts and exposure. We found concordant dyad responses for COVID-19 threat perception, but not for psychological impact. Using the Actor-Partner-Interdependence Model framework, we found that one’s psychological impact was affected by the financial impact from both dyad members. After controlling for risk factors and demographic covariates, we found that family resilience significantly associated with lower COVID-19 psychological impact, though not with threat perception. The findings suggest that both family and individual factors need to be addressed and there may be benefit in addressing multi-level risk and protective factors using an ecological systems approach, which may help prepare the population for future crises.